DC to AC Inverter Prototype for Small Scale Power Supply with SPWM Method - Listyantoro, Fiki; Ma'arif, Alfian; Sharkawy, Abdel-Nasser; Marhoon, Hamzah M. (Peneliti Teknologi Teknik Indonesia, 2023)
Inverter is a device to convert Dc current voltage into AC current voltage. In this article, the inverter is designed using the H-Bridge configuration. The advantage of this configuration is that there is no need for diodes and capacitors to balance the voltage. The main components in designing this inverter are the Arduino Nano, the IR2103 IC, and also the MOSFET. The switching method used is SPWM with H-Bridge configuration which is controlled by 2 IC IR2103. Based on the test results, the output voltage of this inverter is 7.45 Volts. With a DC voltage of 12 Volts. With the use of an oscilloscope that is used to measure the output waveform from the switching results of the MOSFET, the signal is still in the form of a square wave. To make a sine wave, an inductor filter is needed which functions to produce a signal to become a sine wave, and to keep the frequency at 50Hz. The voltage generated from the step-up transformer can be adjusted by rotating the feedback trimpot. The resulting voltage is 88 Vac to 260 Vac. and can accommodate a maximum load of 250 Watts. This inverter is also equipped with a PZEM-004T sensor which functions to read voltage, current, frequency and power data.